Improved Energy Conversion Process With Coupling Induction Motors And Invastigate Unbalanced Operation With Definition Of The Voltage Unbalance - Koopaei, Hossin Rezaei; Eildarabadi, Rahim; Bagheri, Mahmoud Zade (Ciência e Natura, 2015)
This paper assesses Voltage unbalance study as one of power quality issues which is especially effected distribution voltages and is noteworthy. however it is possible that voltage in level of producing and transmission be balanced but this voltages in level of distribution can go out of balance and be unbalanced which is because of unbalanced systems, unequal impedances and lack of appropriate and balanced distribution of one phase loads in distribution systems occurs. In this thesis operation of steady state machine conjunction (Induction motor) under unbalanced voltage will be evaluated. Induction motors in small sizes attach as coupled and will be used instead of big sized induction motors, which is proper for improved electromagnetic systems and more efficient energy conversion mechanism in both symmetric and asymmetric states. Two coupled induction motors can have the same or different rates mechanically. This thesis will analyze coupled machinery using symmetric elements and MATLAB software. Definition of unbalance voltage is used by CVUF factor (complex voltage unbalance factor). Induction motors coupling with DC motors (direct current) is analyzed and coupling effect in electromagnetic torque in all system is studied and comparing of unbalanced voltage on standalone and coupled machines is demonstrateed. The purpose of such comparing is finding the best states in balanced and unbalanced working, also this thesis evaluates the effect of induction motors connection as coupling in energy conversion process.